PENENTUAN KOMODITAS UNGGULAN SUB SEKTOR HORTIKULTUTA DI KABUPATEN MUARO JAMBI - Sadikin, Sadikin; Edison, Edison; Rahman, A (JALOW | Journal of Agribusiness and Local Wisdom, 2021)
The research aims to: (1) determine the commodity horticulture sub-sector of seasonally and superior / base and non-superior / non-base annual and vegetable types in Muaro Jambi Regency during 2014 to 2018; (2) knowing the commodity horticulture sub-sector annual and annual vegetable and fruit types that have fast growth and good competitiveness in Muaro Jambi Regency from 2014 to 2018. Data used secondary data from 2014 to 2018. Analysis tools used in this research are Location Quotient (LQ) and Shift Share. The results of the study inform that (1). Commodities of seasoned vegetables and fruits are long beans, eggplant, beans, cucumbers, spinach and watermelons, which are not superior / non-base are Chinese cabbage / mustard greens, large chillies, cayenne pepper, tomatoes and kale. Commodities of types of vegetables and fruits of superior / base year are duku and pineapple, which are not superior / non-base are durian, siam oranges, mango, jackfruit, papaya, banana, rambutan and sapodilla (2). Types of vegetables and fruits that have a fast growth are Chinese cabbage, long beans, cayenne pepper, eggplant, green beans, cucumber, kale, spinach. Types of vegetables and annual fruits that have fast growth are duku, durian, tangerine, mango, jackfruit, papaya, banana, rambutan, sapodilla. Types of vegetables and annual fruits that have competitiveness are long beans, large chili, cayenne pepper, watermelon. Types of vegetables and annual fruits that have competitiveness are duku, durian, jackfruit, rambutan.